The Effect of Self-Efficacy Training on Nursing Students' Anxiety in Facing The National Objective Structured Clinical Examination (Osce) in Medan City - Basri basri; Afeus Halawa (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The National Objective Structured Clinical Examination (OSCE) is a key graduation requirement for nursing students, but its implementation often triggers anxiety. This anxiety can lower self-confidence, harm academic performance, and in severe cases, even lead to depression. One effective way to address this challenge is through self-efficacy training, helping students build belief in their ability to complete tasks successfully. Strong self-efficacy fosters motivation, effort, and perseverance, which are essential when preparing for OSCE. This study used a quasi-experimental, one-group pretest-posttest design. Training was delivered in eight sessions, each lasting 60 minutes. The population included all nursing students at Prima Indonesia University, Medan, and a sample of 40 students was selected using total sampling. Anxiety levels were measured with the Hamilton Anxiety Rating Scale (HARS), and data were analyzed using a paired sample T-test. The results showed that self-efficacy training significantly reduced students' anxiety in facing the national OSCE (p = 0.001) Keywords: Self-efficacy, Anxiety, Nursing Students, National OSCE